Developing fashion retail operations to growth in emerging markets. Issue 2 (3rd April 2019) - Guercini, Simone; Runfola, Andrea
ABSTRACT: This paper looks at the relations between the rise of emerging markets and the store openings of marketers from advanced countries. It focuses on the retail operations of Italian fashion brands that have opened sales points in order to gain entry into foreign markets. The paper presents an analysis of an expressly developed database of 2, 141 store openings by 311 Italian fashion brands in 322 cities in 82 countries over the period 2006–2015. The analysis highlights a shift of brands stores openings from the developed countries toward emerging markets and discusses the impact of such trend and its relations with the heterogeneity of the firms and markets involved. Some propositions are then formulated regarding the consequences for brand marketers in the developed nations of this ongoing shift of wealth towards the emerging countries.